2014
DOI: 10.1371/journal.pone.0085856
|View full text |Cite
|
Sign up to set email alerts
|

Complex Intra-Operonic Dynamics Mediated by a Small RNA in Streptomyces coelicolor

Abstract: Streptomyces are predominantly soil-dwelling bacteria that are best known for their multicellular life cycle and their prodigious metabolic capabilities. They are also renowned for their regulatory capacity and flexibility, with each species encoding >60 sigma factors, a multitude of transcription factors, and an increasing number of small regulatory RNAs. Here, we describe our characterization of a conserved small RNA (sRNA), scr4677. In the model species Streptomyces coelicolor, this sRNA is located in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…In contrast, only a few sRNAs in streptomycetes have been experimentally characterized so that their function is known. Examples include scr4677, which is thought to impact the actinorhodin production under specific growth conditions (Hindra et al, 2014) and scr3097, which in combination with a riboswitch influences rpf A expression post-transcriptionally (St-Onge and Elliot, 2017). Furthermore, there are the antisense RNA cnc2198.1 that regulates glutamine synthase glnA (D'Alia et al, 2010) and scr5239.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, only a few sRNAs in streptomycetes have been experimentally characterized so that their function is known. Examples include scr4677, which is thought to impact the actinorhodin production under specific growth conditions (Hindra et al, 2014) and scr3097, which in combination with a riboswitch influences rpf A expression post-transcriptionally (St-Onge and Elliot, 2017). Furthermore, there are the antisense RNA cnc2198.1 that regulates glutamine synthase glnA (D'Alia et al, 2010) and scr5239.…”
Section: Introductionmentioning
confidence: 99%
“…The cluster also encompasses genes 384 whose products may contribute to DNA/RNA transactions, including: putative DNA helicase 385 (sco4685), transposase (sco4698), and a homolog of E. coli Rhs protein (rearrangement hotspot 386 protein), which putatively contains the C-terminal toxin domain and is involved in bacterial 387 intercellular competition (Koskiniemi et al, 2013). When we compared the genes in this region to 388 other Streptomyces species, we found the synteny was not strong, perhaps suggesting that some of 389 these genes may have been acquired through horizontal transfer (Hindra et al, 2014). This 390 hypothesis is supported by the notion that mobile elements tend to be sensitive to changes in 391 chromosome topology (Lodge and Berg, 1990).…”
Section: Long-term Supercoiling Imbalance Impacts the Expression Of Dmentioning
confidence: 92%
“…There is growing evidence of complex crosstalk interactions among the even larger number of anti-sigma and anti-anti-sigma factors for this class of σ factor, and it has been suggested that the signal input to regulate these interactions may involve some of the variable, but always multiple, collection of whiJ -like gene sets present in Streptomyces genomes: the clusters include anti-sigma genes of this type and have been implicated in development and antibiotic production 51, 59 . In one such cluster, which is known to influence antibiotic production and differentiation, a small RNA antisense to the Sco4676–4677 intergenic region has been found to have complicated regulatory effects on Sco4676–4677 expression 60 .…”
Section: New Perspectives In Growth and Development Of Streptomycesmentioning
confidence: 99%